Effect of ABO incompatibility on T‐cell flow cytometry cross‐match results prior to living donor kidney transplantation. Issue 4 (7th December 2016) - Lindemann, M.; Lenz, V.; Nyadu, B.; Heinemann, F. M.; Heinold, A.; Guberina, H.; Eisenberger, U.; Lachmann, N.; Schönemann, C.; Kribben, A.; Paul, A.; Horn, P. A.; et al.
Abstract : Background: Due to its high sensitivity, the flow cytometry cross‐match (FCXM) has been described as valuable tool for identifying an optimal donor. We here focused on the impact of ABO incompatibility on FCXM results. Methods: We analyzed 29 ABO incompatible and 89 ABO compatible donor‐recipient pairs (73 and 175 datasets, respectively) prior to living donor kidney transplantation. In all patients, lymphocytotoxic cross‐matches for B and T cells were negative. Results: Recipients with blood group O (A to O and B to O) displayed significantly ( P < 0.05) higher T‐FCXM results than those with blood group A and B (A to B, B to A and AB to A), respectively. Donor‐specific T‐FCXM responses (ΔMFI values) were significantly higher ( P < 0.05) in ABO incompatible vs. compatible pairs (ABO incompatible recipients with blood group O: 32 ± 6; with blood group A: 19 ± 7; with blood group B: 7 ± 4; recipients with ABO compatibility: 3 ± 2, respectively, data represent mean ± SEM). Consistent with the T‐FCXM results donor‐specific isohemagglutinins (IgG titers) were significantly higher in recipients with blood group O vs. A, both prior to rituximab treatment and plasmapheresis/immune adsorption ( P = 0.004) and immediately prior to transplantation, i.e., after rituximab and antibody‐depleting therapies ( P = 0.04). Conclusions: ABO incompatibility was associated with higher T‐FCXM responses, especially in recipients with blood group O. This finding has major impact on the interpretation of flow cross‐match results. Current cut‐off values need to be reassessed in the ABO incompatible setting. © 2016 International Clinical Cytometry Society